Three international agendas: Spain faces its financial, capacitance and policy change limitations - Cascante Hernández, Kattya (Revista Española de Desarrollo y Cooperación, 2023)
In order to achieve a successful implementation of the three international agendas (development, financing and sustainability) that will be approved in September 2015, three elements turn out to be mandatory: the transfer of sufficient financial resources, an enforcement of capacities and a predisposition to policy changes. Without these three conditions the current Spanish government, unless a last minute change, will be ill-equipped to meet and carry out the upcoming international commitments.
Keywords: Agenda; Financial resources; Spanish government; International commitments